Variety perception and attitude toward digital assortments. Issue 12 (17th July 2019) - Piris, Yolande; Guibert, Nathalie
Abstract : Purpose: The purpose of this paper is to investigate consumers' variety perception for online grocery assortments and, more generally, to better understand consumers' attitude toward digital assortments. In particular, this research examines the influence of the organization of products that results from assortment structure and display. Design/methodology/approach: Starting from the observation that previous work on traditional assortments is not sufficient to understand consumers' perceptions and attitudes, the paper adopts a hypothetico-deductive approach and develops four hypotheses. These hypotheses are tested using an experimental approach. Findings: This research enables us to see that both attitude and variety perception are affected by the way products are organized on a website. Furthermore, contrary to what the literature on traditional assortments allows one to assume, the assortment corresponding to a more positive attitude is not perceived as being the more varied. As a result, our findings reconsider the link between variety perception and consumer assortment evaluation for digital assortments. Research limitations/implications: The work is based on data collected for only one product category. It would be interesting to explore other categories also, to determine if the structure of the assortment and variety perception have stable effects. Practical implications: The results inform retailers that they must carefully design the display of their digital assortments. If a retailer wants to enhance variety perception, the authors recommend using an assortment organized by brand, or presenting all the products together. If, instead, the goal is to encourage a positive attitude, the retailer should opt for assortments sorted by attribute or that present all products together. Originality/value: This research adopts a new orientation on assortment perception and evaluation, considering the specificities involved in digitizing assortments. In addition, this research studies a real product category and puts respondents in experimental conditions close to reality.